The Epidemiology of Trauma Patients Attended by a Paramedic Staffed Emergency Medical Service in Perth, Western Australia - Brown, Elizabeth Emma (Curtin University, 2019)
This thesis examined the characteristics and outcomes of adult trauma patients attended by paramedics in the metropolitan area. An increase in the incidence rate of trauma especially in older adults was found, with more than half of those transported to hospital being over 51 years of age. Falls from standing were found to be the most common cause of major trauma and older age was associated with a significantly reduced likelihood of Trauma Centre transport.